Faulty scenarios in the investigation - Gutiérrez Gómez, Edgar (2020)
The current phenomenon that humanity is experiencing leads to a serious turn to the stage of scientific research. Fundamental aspect that generates alternative solutions to the vicissitudes of nature that we face in human coexistence. Research in Peru and in other parts of the world, was lagged by sumptuary situations of the ephemerality of immediate satisfaction. The consequences for dealing with epidemics and social problems are evident in public health and the social chaos that is generated in the absence of alternatives for social research.